A reforma universitária e a Universidade de São Paulo: década de 1960 - Celeste Filho, Macioniro (2006)
This thesis dissertation refers to the University Curriculum Reform occurred at the end of the 60 s. Since the beginning of the 60 s, Brazilian intellectuals mainly professors have criticised its programmes by showing new paths for renewing them. Among those changes were the replacement of cathedra by the departmental system, and the Faculdades de Filosofia, Ciências e Letras (Faculties of Philosophy, Sciences and Literature) by the fundamental institutes of science. These proposals will be presented followed by their discussions in the academic periodicals. Between the years of 1967 and 1968, the debates about the creation of a law of University Reform reached their culmination. On November 28, 1968, the Law number 5.540 that reformulates the Brazilian graduation courses is sanctioned two weeks before the political fights of the time - the Ato Institucional number 5 (public document that exposes an authority s deliberation). The Law number 5.540 and the Ato Institucional number 5 appeared as the summit of the students conflicts and the military dictatorship authoritarian escalation. The connections between those decisive episodes to the present Brazilian reality will be presented here. And as the last matter, the implantation of the University Reform in the main Brazilian institution for higher education the São Paulo University between 1968-1969